2012
DOI: 10.3892/ijmm.2012.878
|View full text |Cite
|
Sign up to set email alerts
|

NOD1 and NOD2 stimulation triggers innate immune responses of human periodontal ligament cells

Abstract: Nod-like receptors (NLRs) are cytosolic sensors for microbial molecules. Nucleotide-binding oligomerization domain (NOD)1 and NOD2 recognize the peptidoglycan derivatives, meso-diaminopimelic acid (meso-DAP) and muramyl dipeptide (MDP), respectively, and trigger host innate immune responses. In the present study, we examined the function of NOD1 and NOD2 on innate immune responses in human periodontal ligament (PDL) cells. The gene expression of NOD1 and NOD2 was examined by RT-PCR. IL-6 and IL-8 production in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 37 publications
1
38
0
2
Order By: Relevance
“…The present results were supported by that the enhanced IL8 mRNA expression was markedly suppressed in NOD2-and NOD1-silenced cells and the combinatory dual signaling through extracellular TLRs and intracellular NODs might lead to the synergistic activation of innate immune responses in host cells [24]. Toll-like receptor (TLR) stimulation has been reported to lead to increased gene expression of NOD1 and NOD2 in human periodontal ligament cells [25]. TLR2-TLR4 double-deficient mice are susceptible to Salmonella typhimurium, a Gram-negative bacterium [26].…”
Section: Discussionsupporting
confidence: 71%
“…The present results were supported by that the enhanced IL8 mRNA expression was markedly suppressed in NOD2-and NOD1-silenced cells and the combinatory dual signaling through extracellular TLRs and intracellular NODs might lead to the synergistic activation of innate immune responses in host cells [24]. Toll-like receptor (TLR) stimulation has been reported to lead to increased gene expression of NOD1 and NOD2 in human periodontal ligament cells [25]. TLR2-TLR4 double-deficient mice are susceptible to Salmonella typhimurium, a Gram-negative bacterium [26].…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, a similar synergy between NOD2 and TLR2 signaling is observed in cells from this site, whereby co-triggering with ligands of these PRRs synergistically enhances the expression of IL-6 and IL-8 via a p38MAPK-dependent mechanism (16). Synergy in multiple PRR signaling pathways has also been reported (17), and it has been suggested that such synergy may be specific to the TLR2 and NOD2 signaling pathways in stromal cells isolated from the oral mucosa (18, 19). A major outstanding question is whether the signaling pathways underlying the synergy between simultaneous NOD2 and TLR2 triggering are conserved between myeloid and stromal cells or whether cell type-specific pathways result in broadly similar transcriptional and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported TLR stimulation led to increased gene expression of NOD1 and NOD2 in HPDLFs (Jeon et al . ). Moreover, LPS pretreatment enhanced the activation of NF‐κB, ERK and JNK by MDP in hepatocytes (Scott et al .…”
Section: Discussionmentioning
confidence: 97%